2018
DOI: 10.5114/aoms.2016.63597
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25-Foxp3+ T cells as a marker of disease activity and organ damage in systemic lupus erythematosus patients

Abstract: IntroductionT regulatory cells (Treg) play an important role in the maintenance of immune cell homeostasis, as it has been reported that CD4+CD25+ T cells suppress the auto-reactive responses in autoimmune diseases such as systemic lupus erythematosus (SLE). The clinical significance of the recently identified population of CD4+CD25-Foxp3+ T cells and whether they are associated with particular organ involvement is still not clear. So, the aim of our study was to evaluate the presence of CD4+CD25-Foxp3+ cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…23 No statistically correlation between CD4 + CD25 + Foxp3 + Treg cells % and hematological indices was found in our study which comes in contrary with other studies that found a positive correlation with hematological manifestations including thrombocytopenia and leucopenia and this might be explained by the overlap of organ manifestation, as most SLE patients suffer from hematologic manifestations as well as renal involvement. 24,25 Our result showed a significant negative correlation between CD4 + CD25 + Foxp3 + Treg cells % and SLEDAI-2K in patients with SLE. This is in concordance to the findings of other studies that found that Foxp3 expression in circulating CD4 + CD25+Treg cells derived from SLE patients inversely correlates with disease activity.…”
Section: Discussionmentioning
confidence: 52%
“…23 No statistically correlation between CD4 + CD25 + Foxp3 + Treg cells % and hematological indices was found in our study which comes in contrary with other studies that found a positive correlation with hematological manifestations including thrombocytopenia and leucopenia and this might be explained by the overlap of organ manifestation, as most SLE patients suffer from hematologic manifestations as well as renal involvement. 24,25 Our result showed a significant negative correlation between CD4 + CD25 + Foxp3 + Treg cells % and SLEDAI-2K in patients with SLE. This is in concordance to the findings of other studies that found that Foxp3 expression in circulating CD4 + CD25+Treg cells derived from SLE patients inversely correlates with disease activity.…”
Section: Discussionmentioning
confidence: 52%
“…In the analysis of Tregs/CD4 + T-cells, the proportion of Tregs among CD4 + T-cells in SLE patients was decreased relative to that for HCs (REM −0.79, 95% CI −1.53, −0.05; p = 0.037; Figure 3). 9,10,13,14,16,25,27–43 The I 2 statistic indicated an extreme heterogeneity of 97.5%.
Figure 2Forest plots generated by meta-analysis for the significant findings about Tregs/PBMCs in SLE patients and HCs.
…”
Section: Resultsmentioning
confidence: 99%
“…Further studies are also needed to detect other potential markers of disease progression including lung involvement. For example, it might be interesting to assess regulatory T-cells CD4+CD25-FoxP3 (Tregs) that are associated with disease activity and organ damage in systemic lupus erythematosus (SLE) [14].…”
Section: Discussionmentioning
confidence: 99%